Increasing nickel concentrations in a large river network of South Tyrol, Eastern European Alps - Brighenti, S.; Bearzot, F.; Delpero, M.; Tirler, W.; Tolotti, M.; Vorhauser, S.; Bachmann, C.; Romanin, E.; Sparber, K.; Vidoni, B.; Fogale, F.; Comiti, F. (ACS ES&T Water, 2025)
Climate change and cryosphere degradation may enhance the concentrations of heavy metals in high-mountain rivers. However, the downstream export of these contaminants to lower elevations is still overlooked. In this study, we investigated the spatial and temporal patterns of dissolved and bioavailable nickel concentrations in the upper Etsch/Adige river basin (1590 km2; 54 sites) during the period of 2005−2023. Furthermore, we investigated the same concentrations seasonally (2022−2023) along a tributary (Schnals/Senales River), from the glacier origin down to the confluence with the Etsch River (13 sites). Concentrations of both nickel forms increased during the past decade by up to 4 times, yet only in river reaches draining the acidic metamorphic Ötztal Unit. Sulfide oxidation, more intense at sites featuring larger glaciers, rock glaciers, and permafrost extent in their catchment, enhanced nickel concentrations. Along the Schnals River, values were elevated in the proglacial waters (dissolved fraction up to 112 μg L−1), gradually decreased moving to lower elevations, and dropped (from 20 to 30 to 2−5 μg L−1) downstream of a large reservoir. Currently, bioavailable nickel concentrations exceed the EU environmental quality standards at 40% of the investigateinvestigated sites, demonstrating sharp environmental implications that may be extended to other similar geological and cryospheric settings.